Use of Performance Focused Activity Based Costing (PF-ABC) Method in Measuring / The Costs Health Service - Practical Study Ibn Al-Atheer Educational Hospital for Children (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The research aims to measure the cost of health services for the main activities and assistance at Ibn al-Athir educational hospital for children by applying performance-based activity-based costing method (PF-ABC), the research assumes that the use of the performance-based activity-based costing method (PF-ABC)  assist in accurately measuring the cost of health services for the main activities and assistance in the hospital sample research, and the research is based on inductive method through applying at Ibn al-Athir educational hospital for children, and the research reached a set of conclusions, the most important of which is the use of the (PF-ABC) method  which helps to measure the cost of health services for key activities and assistance more accurately, as a result, this contributes to reduce the utilized energy through the optimal utilization of the elements of the health institution this leads to the achievement of the objective of improving the quality of the service produced and reducing its cost for the hospital itself.